Potentials of kawayang tinik (Bambusa blumeana) as new source antimicrobial agents - Saducos, Abegail G (Plant Science Today, 2022)
In this time where health is priority and surges of microbial resistance is highly observed within the society, discovering new, effective and sustainable sources of potential pharmacologic products is highly significant. The study explored the antimicrobial potentials of the different parts of Bambusa blumeana (kawayang tinik), a common Philippine bamboo species, against selected pathogenic bacterial and fungal species utilizing minimum inhibitory concentration via agar well diffusion method. Results of the study showed that extracts of B. blumeana, specifically the leaf, rhizome, roots, inner and outer culms, are capable of inhibiting microbial growth at 0.06 to 0.98 mg/ml concentrations. Specifically, the aqueous outer culm extract of B. blumeana proved to be most effective in inhibiting the growth of Pasteurella multocida at 0.24 mg/ml while Staphylococcus aureus and Escherichia coli were most susceptible to ethanolic outer culm extracts at 0.06 mg/ml and 0.12 mg/ml respectively. Bacillus subtilis, on the other hand, was observed to be the most sensitive to ethanolic root extracts at 0.06 mg/ml. Furthermore, Aspergillus niger was observed to be susceptible to ethanolic rhizome extract (0.24 mg/ml) while the ethanolic leaf, roots, inner and outer culms were equally effective in inhibiting Penicillium chrysogenum at 0.98 mg/ml extract concentration. Phytochemical testing further revealed the presence of phenols and flavonoids in the different parts of the bamboo species which further support its potential as a new source of pharmaceutical biocompounds.